2021
DOI: 10.1016/j.omto.2020.09.005
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-130b-3p contained in MSC-derived EVs promotes lung cancer progression by regulating the FOXO3/NFE2L2/TXNRD1 axis

Abstract: This study aimed to explore the molecular mechanism by which mesenchymal stem cells (MSCs) mediate lung cancer progression. Extracellular vesicles (EVs) were isolated from transfected or untransfected MSCs, and were co-cultured with lung cancer cells with/without microRNA-130b-3p (miR-130b-3p) inhibitor, mimic, overexpression plasmids of FOXO3/NFE2L2, or shRNAs. CCK-8 assay, colony formation, transwell assay, and flow cytometry were carried out to determine the biological functioning of lung cancer cells. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Another concern for the use of MSC-derived EVs in the clinical context is the potential involvement of deleterious processes mediated by specific miRNAs. For example, miR-130b-3p in MSC-derived EVs has been shown to promote lung cancer cell proliferation, migration and invasion ( Guo et al, 2021 ) and exacerbates I/R injury after adoptive transfer in diabetic mice ( Gan et al, 2020 ). With the aim of identifying miRNAs responsible (at least in part) for the beneficial effects attributed to EVs, we analyzed miRNA content in MSC derived EVs and investigated a miRNA with cardioprotective features when transplanted as a single molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Another concern for the use of MSC-derived EVs in the clinical context is the potential involvement of deleterious processes mediated by specific miRNAs. For example, miR-130b-3p in MSC-derived EVs has been shown to promote lung cancer cell proliferation, migration and invasion ( Guo et al, 2021 ) and exacerbates I/R injury after adoptive transfer in diabetic mice ( Gan et al, 2020 ). With the aim of identifying miRNAs responsible (at least in part) for the beneficial effects attributed to EVs, we analyzed miRNA content in MSC derived EVs and investigated a miRNA with cardioprotective features when transplanted as a single molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, miR-199, via stimulation of the mTOR pathway, increases the chemo-sensitivity of hepatocellular carcinoma cells [ 65 ]. In contrast, miR-208a induces proliferation, migration, and invasion of osteosarcoma cells [ 66 ] and two miRNAs, miR-21-5p and miR-130b-3p, promote the growth and mobility of two types of lung cancer by regulating their FoxO3 axis [ 67 , 68 ].…”
Section: Role Of Mscs and Msc-evsmentioning
confidence: 99%
“…MSC-derived EVs in rat models with traumatic brain injury and ischemic brain injury has been shown to increase angiogenesis and neurogenesis, thus improving functional recovery. 129 , 130 Katsuda et al suggested a new treatment possibility using EVs that carry neprilysin, an amyloid degrading enzyme as a cell-free drug therapy for Alzheimer's disease, 131 , 132 Figure 1 .…”
Section: Evs In the Treatment Of Neurological Illnessesmentioning
confidence: 99%